Cigarette Taxes and Smoking in the Long Run - Andrew I. Friedson; Daniel I. Rees (Institute of Labor Economics (IZA), 2020)
Researchers have focused on the contemporaneous relationship between cigarette taxes and smoking, while the longer-run effects of cigarette taxes have received little attention. Using individual-level panel data from 1970-2017, we estimate the effects of cigarette taxes experienced as a teenager on smoking later in life. We find that a one-dollar increase in the cigarette tax experienced between the ages of 12 and 17 is associated with substantial reductions in smoking participation and intensity among adults in their 20s through mid-60s. Among first-time mothers, it is associated with a reduction in the likelihood of smoking the year of giving birth.
Keywords: H2; I10; I12; 330; smoking; cigarette taxes; long run